The effectiveness of public administration of sports in rural communities under decentralization (experience for Ukraine) - Dorofieieva, Tеtіana (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
The aim of this study was to examine the effectiveness of public administration of sport in rural communities of Ukraine through the prism of a comparative analysis of the experience of European countries in this sphere. General scientific methods (analysis and synthesis) and public management methods (expert assessment, comparative analysis) were involved. The results showed that before the beginning of decentralization, the Ukrainian system of financing and management of sports developed according to the French model—with a certain centralization of the management of state structures and vertical reporting. At the same time, it has been established that under the new realities such a system will not be able to function, which is already noticeable based on reports on the financing of the industry. Starting from 2015, local budgets (including those of rural communities) gradually invested much more in the development of sports than the state budget. Accordingly, a logical step would be their initiative in the development of the sports sphere, particularly in mass sports. Based on the practices of European countries, the Ukrainian authorities need to introduce practices of more active involvement of sponsors.